Analisis Fitokimia Ekstrak Bulung Boni (Caulerpa spp.) dan Uji Daya Hambatnya terhadap Fungi Fusarium moniliforme (Sacc.) Nirenberg - TANDYA, VICKY; WIRAWAN, I GEDE PUTU; SUADA, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.2, April 2021, 2021)
Phytochemical Analysis Of Bulung Boni Extract ( Caulerpa s pp.) a nd Its Inhibiting Ability Against Fusarium moniliforme (Sacc.) Nirenberg Seaweed is a marine biota that produces bioactive compounds which are useful for the development of the pharmaceutical industry. Caulerpa spp. is a green algae that is commonly consumed as vegetables or fresh vegetables by tropical communities, but the use of Caulerpa spp. in other fields is not optimal. The purpose of this study was to determine the content of antifungal compounds in the extract of  Caulerpa spp. and antifungal activity against F. moniliforme . The research method used was Gas Chromatography and the diffusion well method with 14 treatments and 3 replications. The design used was completely randomized with ANOVA analysis followed by Duncan's test with a confidence level of 5%. The results showed that the ethanol is extract of Caulerpa spp. has antifungal compounds, namely alkaloids, saponins, and organic acids which indicated fungistatic effect. Ethanol extract of Caulerpa spp. had minimal antifungal activity (MIC) against F. moniliforme at a concentration of 0.6% with an inhibition zone diameter of 5 mm and was categorized as weak. The best extract concentration in inhibiting F. moniliforme in the treattested was a concentration of 5% with an inhibition zone diameter of 13.67 mm and a percentage was 54.54% colony inhibition.